Assessment of organic acid accumulation and its related genes in peach. (1st January 2021) - Zheng, Beibei; Zhao, Li; Jiang, Xiaohan; Cherono, Sylvia; Liu, JingJing; Ogutu, Collins; Ntini, Charmaine; Zhang, Xiujun; Han, Yuepeng
Highlights: Degradation of organic acids caused low acidity of peach fruits. Malate accumulation is controlled at the level of metabolism and vacuolar storage. Citrate accumulation is controlled at the level of metabolism. Seven candidate genes for peach fruit acidity were identified. Abstract: Fruit acidity is an important determinant of peach organoleptic quality, but its regulatory mechanism remains elusive. Measurement of organic acids in ripe fruits of seventy-five peach cultivars revealed the predominant components malate and citrate, accompanied by quinate. Organic acid accumulation increased at early stages of fruit growth, but exhibited a more dramatic reduction in low-acid cultivar during later stages of fruit development compared to high-acid cultivars. Low-acid cultivars showed citrate degradation and less transport of malate into the vacuole due to up- and down-regulation of a GABA pathway gene GAD and a malate transporter gene ALMT9, respectively. The NAD-MDH1 gene might control the rate-limiting step in malate synthesis, while three genes, PDK, PK, and ADH, could affect citrate synthesis through the pyruvate-to-acetyl-CoA-to-citrate pathway. Altogether, these results suggested that malate accumulation is controlled at the level of metabolism and vacuolar storage, while metabolism is crucial for citrate accumulation in peach.